1988
DOI: 10.1295/polymj.20.597
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Li+ Ion Transport Numbers in Poly(ethylene oxide)–LiX Complexes

Abstract: ABSTRACT:The transport number for Li+ ions in Poly(ethylene oxide)-LiX complexes was measured using a potentiostatic polarization technique. The results indicate that the Li+ 10n transport is strongly influenced by the salt concentration and the type of counter ions.KEY WORDS Transport Number / Poly(ethylene oxide) / Salt / Polarization / Lithium / Lithium ion conducting polymer materials are being intensively investigated in a number of research laboratories because of their potential use as solid electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 6 publications
4
19
0
Order By: Relevance
“…The P(EC/EO)/LiFSI electrolyte (160 mol%) also had a very high t + of 0.66 (see also Figure S6, Supporting Information). In contrast, the PEO electrolyte (5 mol%) had a very low t + value of 0.13, matching the values reported by many researchers . Based on values of the ionic conductivity and t + , the Li + conductivities (σ × t + at 60 °C) of P(EC/EO)‐, PEC‐, and PEO‐based electrolytes were estimated to be, respectively, 0.32, 0.041, and 0.045 mS cm −1 for the concentration of the best performing electrolytes.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The P(EC/EO)/LiFSI electrolyte (160 mol%) also had a very high t + of 0.66 (see also Figure S6, Supporting Information). In contrast, the PEO electrolyte (5 mol%) had a very low t + value of 0.13, matching the values reported by many researchers . Based on values of the ionic conductivity and t + , the Li + conductivities (σ × t + at 60 °C) of P(EC/EO)‐, PEC‐, and PEO‐based electrolytes were estimated to be, respectively, 0.32, 0.041, and 0.045 mS cm −1 for the concentration of the best performing electrolytes.…”
Section: Resultssupporting
confidence: 83%
“…[5] PEObased electrolytes exhibit relatively high ionic conductivity. Nevertheless, PEO-based electrolytes have very low Li transference numbers (t + ), [6][7][8] because cations form a quasi-cross-linking structure with polar ethereal oxygen atoms. [5] The resulting slow Li + conduction should be improved for use in various battery applications.We focus on polycarbonates as a novel matrix for SPEs.…”
mentioning
confidence: 99%
“…This value is very high relative to the typical polyether-based electrolytes, for example, t þ B0.1 for PEO 2 LiBF 4 (B51.6 wt%) at 100 1C. 18 According to a previous report, the t þ drastically decreases with increasing salt concentration in PEO. 18 Those authors suggested that the decreases in t þ are caused by the decrease in the number of free PEO segments and that the motion of Li þ is hindered by the subsequent formation of ion-pairs.…”
Section: Resultsmentioning
confidence: 79%
“…18 According to a previous report, the t þ drastically decreases with increasing salt concentration in PEO. 18 Those authors suggested that the decreases in t þ are caused by the decrease in the number of free PEO segments and that the motion of Li þ is hindered by the subsequent formation of ion-pairs. However, the PEC electrolyte has a very high t þ value, in spite of the high salt concentration.…”
Section: Resultsmentioning
confidence: 85%
“…5 Munshi et al have also reported that crystalline PEO-based electrolytes also show low values less than 0.2 at Li salt concentration higher than 30 mol%. 12 It is well known that, in the polyether electrolyte, dissociated Li + stable interact with dipoles of ether oxygens in the polymer chains where the transference number is lowered. Figure 2 shows the relation between transference numbers and the radius of anions dissociated into PEC electrolytes.…”
Section: Resultsmentioning
confidence: 99%